TINJAUAN BAURAN PEMASARAN BLU BY BCA DI ERA DIGITAL BANK - Raden Roro Velma Lucretia Daniswara (2023)
During the pandemic, the demand for digitalisation arises due to changing public expectations for faster and more efficient financial services. The purpose of writing this Final Project is to find out the Blu by BCA feature, the marketing mix, and the impact of the marketing mix felt by BCA Digital. The data collection method used is the secondary data collection method through literature review. The data that has been collected will be analysed with a descriptive method that aims to describe the marketing mix of Blu by BCA. Blu is a Digital Bank application under the control of PT Bank Digital BCA. BCA Digital has different segments and strategies from conventional banks, but BCA Digital's infrastructure still adapts to BCA's channels. In this era of tight digital banks, BCA Digital is improving service quality and implementing an effective marketing mix. With user-friendly application features, Blu makes it easy for Millennial and Gen Z customers to transact. BCA Digital applies the 7P marketing mix elements, namely product, price, place, promotion, people, process, physical evidence. The increasing public interest in using digital banks for ease of transactions is the focus of BCA Digital going forward.